The Raptors of Iowa - Landenberger, James F. (Book collections on Project MUSE., 2013)
This collection of James Landenberger's paintings of Iowa birds of prey presents thirty-two full-page, full-color species, from the common turkey vulture to the red-shouldered hawk of Mississippi River woodlands to the little northern saw-whet owl. Four naturalists who have devoted their lives to conserving wilderness habitats and species have written essays to complement the paintings.